A realização da justiça fiscal por meio da efetivação de princípios tributários - Martins Filho, Luiz Dias (2016)
Analyzing legal systems and tax principles, we realize that there are true legal and economic canons of taxation that states of international society can not underestimate, otherwise they will pay penalties as driven these states or countries to the margin or even the exclusion of the international economic integration and globalization processes. As a consequence, these states will face less competitiveness and loose part of international commercial trade, besides they will suffer the results of legal, economic and political isolation. This research makes an inquiry if the Brazilian tax system follows the five basic principles or canons of taxation described by Adam Smith, that in a summarized way are: (i) people should contribute taxes in proportion to their incomes and wealth; (ii) taxes should be certain, not arbitrary; (iii) taxes should be levied in the most convenient way; (iv) the costs of imposing and collecting taxes should be kept minimal; and (v) taxes should be competitive internationally. These tax principles are observed in a higher or lower degree by all tax systems in the world, with the purpose to assure, particularly, fundamental rights. This work also makes an inquiry if tax justice is delivered through the effectiveness of these basic tax principles that for a long time had been given by Adam Smith. This tax justice delivery is analyzed in a context of a social-democratic and pluralist country like Brazil, particularly according to an equalitarian liberalism in a neo-contratualist perspective